A technique to reduce correlated errors in continuous monitoring applications - Mat Amin, Zulkarnaini; David R., Twigg (2001)
GPS techniques are now being used extensively in many monitoring applications such as engineering structures, landslides and crustal deformation. In most cases, the attainable accuracy of GPS measurements is dependent upon the presence of errors or noises in the measurements. Some of the errors can be eliminated or minimised by differencing techniques, but others require particular attention if a high accuracy result is sought. This paper presents various experiments on kinematic GPS surveys, from which a method to reduce GPS errors has been established. The method is based on transferring the error from one station to another where the two stations are highly correlated. Three GPS stations were involved: the first was located at a known reference station, the second at fixed station near the object being monitored and the third positioned on the object itself. It is the strong correlation between the latter stations that enables corrected co-ordinates to be determined. Results from the tests show that by applying the aforementioned method, the final GPS measurements are more accurate for use with continuous monitoring applications.